Unabhängige Organisationen in autoritären Regimes: Widerspruch in sich oder effektives Instrument von Developmental States? - Joachim Ahrens; Manuel Stark (PFH Private Hochschule Göttingen, 2012)
– This contribution explores the importance of independent organizations in authoritarian regimes. While some authoritarian governments delegate policy tasks to (relatively) autonomous agencies simply in order to improve their domestic or international image as modern political leaders or to build up democratic facades to conceal the actual nature of their regime, other political leaders do so in order to make their genuine commitment to economic growth and development more credible. This relates to the central questions of this paper: Why do political elites in authoritarian regimes craft, or accept the emergence of, (relatively) independent organizations? Which specific forms and functions of these organizations can be identified? The main observation of this paper is that authoritarian governments of so-called developmental states have effectively used (relatively) independent organizations in order to implement market-oriented reforms, to improve private-sector coordination, and to foster economic growth and development in the long run.
Keywords: 330